1998
DOI: 10.1002/j.2050-0416.1998.tb01004.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Kilning on the Capability of Malt to Oxidise Lipids

Abstract: The influence of kilning on the ability off malt to oxidise lipids was studied. Barley was malted with a standard programme and subsequently dried with varying kilning procedures. The capability of samples taken during kilning to oxidise lipids was determined by the lipoxygenase (LOX) reaction, i.e. by measuring O2 consumption in an aqueous suspension of samples upon addition of excess amounts of exogenous linoleic acid. Various kilning programmes from isothermal low-temperature kilnings to kilnings with varyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Trans-2-nonenal, a common staling compound in beer, is formed from oxidized lipid components. Lipid oxidation in malt has also been reported to cause lautering (filtering) problems during the brewing process and contribute to some downstream off-flavors ( Kaukovirta-Norja et al., 1998 ; Su et al., 2022 ). In recent years, an effort to create low-lipoxygenase malt (LOX-less) has been made.…”
Section: Malt Metabolite Chemistry: Role Of Lipidsmentioning
confidence: 99%
“…Trans-2-nonenal, a common staling compound in beer, is formed from oxidized lipid components. Lipid oxidation in malt has also been reported to cause lautering (filtering) problems during the brewing process and contribute to some downstream off-flavors ( Kaukovirta-Norja et al., 1998 ; Su et al., 2022 ). In recent years, an effort to create low-lipoxygenase malt (LOX-less) has been made.…”
Section: Malt Metabolite Chemistry: Role Of Lipidsmentioning
confidence: 99%
“…LOX enzymes are thermally inactivated, thus a reduction in enzymatic oxidation of unsaturated fatty acids is expected particularly at the onset of the wort production process. However, during malting LOX activity was shown previously 169 to increase mainly in the first 2 -6 hours of kilning, thus the risk to oxidise lipids remains at moderate kilning temperatures. Dong et al 159 , for example, showed that the trans-2-nonenal concentrations greatly increased when producing crystal malts compared to the corresponding green malt.…”
Section: Flavour and Aroma Compoundsmentioning
confidence: 92%
“…This system enabled production of malt with a lower concentration of hexanal. In the case when LOX activity is high and oxygen is present in the system, enzymatic oxidation and auto‐oxidation take place resulting in a decrease during germination and following it kilning, in the levels of triglycerides and a subsequent increase in free fatty acids, intermediates of trans ‐2‐nonenal and hexanal, respectively ( 146,167,168 ) . This is most likely due to both LOX activity and lipid metabolism of the grain.…”
Section: Evolution Of Marker Aldehydes and Their Precursors During The Malting Processmentioning
confidence: 99%
“…Hence the bottom layer dries faster and enzyme inactivation occurs quicker than in the top layer ( 56 ) . Therefore, the moment of inactivation mostly depends on the position of a kernel in the bed and the particular properties of the enzyme under consideration ( 56,61,145,166,168,180,181 ) . As an example, Baxter ( 61 ) stated that lipoxygenase activity in green malt is relatively stable; however, a temperature increase up to 65°C reduces its activity by 70‐90% depending on the time of grain exposure to the high temperature.…”
Section: Evolution Of Marker Aldehydes and Their Precursors During The Malting Processmentioning
confidence: 99%
See 1 more Smart Citation